Prinsip Dasar HAM Dalam Terminologi Doktrin Hukum Islam: (Penelaahan Ayat Dalam Al-Qurán dengan Tafsir Maudhu'iy) - Budiarti Budiarti (Al-Mizan, 2015)
This study suggests the basic concepts and forms of Human Rights (HAM) in the Koran as the basic source of Islamic law since the beginning diperdebatkannya until today. Forms of human rights in the Qur’an, such as freedom, equality, and justice. It seems clear that Islamic law has a strong foundation in the issues of human rights. Even in the particular context of human rights in Islam went one step further than the Western version of human rights. Islamic law not only recognizes human rights as an essential part of the rights and be in a position of primary needs.